DAMPAK ARTIFICIAL INTELLIGENCE TERHADAP PEMBELAJARAN IPA/FISIKA DI SEKOLAH - Gontina, Wulan; Asyhar, Rayandra (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
The evolutionary era of Industry 4.0. and the era of society 5.0. make changes to learning activities at school. The use of science/physics learning media, methods and models based on Artificial Intelligence is able to visualize science/physics learning material which is mostly abstract in nature. The teacher's role in making science/physics learning activities effective, interactive and communicative is very large. For this reason, teachers need to increase their insight and upgrade their knowledge of Artificial Intelligence-based digital technology so that learning objectives can be achieved effectively. Of course, the application of Artificial Intelligence in accordance with the material taught in science/physics lessons will make learning activities more interesting and have a positive impact on the progress of education in Indonesia. Even though the positive impact of Artificial Intelligence is more dominant than the negative impact, it is necessary to anticipate the negative impact of using AI in science/physics learning so that progress in the education sector becomes more efficient, effective and safe in the future.